PENATALAKSANAAN ACTIVE STRETCHING DAN HAND EXERCISE UNTUK MENCEGAH CARPAL TUNNEL SYNDROME DALAM PENGGUNAAN SMARTPHONE DI KELURAHAN KAUMAN KECAMATAN BATANG KABUPATEN BATANG - Eko Budi Prasetyo; Anna Maulidia Khairunissa (LPPM Universitas Pekalongan, 2021)
Some people do not realize that using a smartphone is addictive so that it affects the health of the body and can make someone lose track of time. Excessive use will cause several effects, including eye fatigue, neck muscle stiffness, as well as stiff and tingling hands. From the observation process of identifying physiotherapy problems, it was found that the complaints experienced by the family community were that sometimes there was pain and tingling in the wrist area due to the use of smartphones, computers, and household activities after long-term activities. This observation process is carried out using the assessment method. The purpose of this activity is to provide knowledge and insight to the general public as well as improve the health status of the community, introduce physiotherapy, provide exercise programs in the form of Active Stretching and Hand Exercise in the prevention of Carpal Tunnel Syndrome. Prior to outreach and training, the community was given a pretest and the community was given a post test after completing the activity. The results and conclusions obtained from the pre-test and post-test are that there is an increase in people's knowledge after counseling and training.Keywords : Carpal Tunnel Syndrome, Active Stretching, Hand Exercise